Analisis Perputaran Modal Kerja pada Perusahaan Umum Daerah (PERUMDA) Air Minum Kabupaten Toraja Utara - Datu Ma’dika; Dwibin Kannapadang; Ade Lisa Matasik (Politeknik Kampar, 2023)
The purpose of this study was to analyze the level of working capital turnover at the Regional Public Company (PERUMDA) Drinking Water in North Toraja Regency. The type of research used is a type of quantitative descriptive research. The results of the study show that working capital turnover at PERUMDA Water Supply Toraja Utara for the 2020 – 2022 period is less effective and efficient according to industry standard working capital turnover criteria but the ratio value increases every year. In 2020, working capital turnover is 2.09 times, which takes 172 days. In 2021, working capital turnover will decrease to 2.05 times, which will take 176 days. This year, the working capital turnover ratio will increase. In 2022 working capital turnover will increase by 2.47 times which takes 146 days and this year the value of the working capital turnover ratio has increased..